The moderating roles of managerial discretion and absorptive capacity in the relationship between entrepreneurial social networks' structural holes and new venture revenue growth in China - Wang, Yi (2020)
In a new venture context and at the firm level, this doctoral thesis aims to investigate the moderating effect of two constructs, entrepreneurial managerial discretion and organizational absorptive capacity, to the potentially contingent relationship between entrepreneurs’ social network structural holes and new ventures’ financial performance (specifically their revenue growths). For that, it comprises of two separated but connected studies, including a quantitative study (Study 1) and a qualitative case study (Study 2).